1986
DOI: 10.1099/00221287-132-9-2433
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of an O-Methylglucose-containing Lipopolysaccharide Produced by Nocardia otitidis-caviarum

Abstract: The low-Mr lipopolysaccharide produced by Nocardia otitidis-cavirum is composed of 6-O-methyl-D-glucose (11 mol), D-glucose (8 mol) and 3-O-methyl-D-glucose (1 mol). Glyceric acid was also found as a constituent. Methylation and periodate oxidation analyses suggested that the backbone was formed by (1----4)-linked glucose and O-methylglucose residues. Glucose (1 mol) and 6-O-methylglucose (1 mol) served as branching points. Acetic acid was the major acyl substituent esterifying glucose residues. The lipopolysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…3B) ϩ ) in the MALDI mass spectrum run in the positive ion detection mode (data not shown). This result thus confirmed that the complex MGLP pattern described above resulted from variable combinations of acylation of mainly two oligosaccharide backbones, MGP 19,12 and MGP 20,12 , and, to a much lesser extent, MGP 20,11 and MGP 20,13 .…”
Section: Construction Of M Smegmatis and M Tuberculosis Glucosyltrasupporting
confidence: 81%
See 3 more Smart Citations
“…3B) ϩ ) in the MALDI mass spectrum run in the positive ion detection mode (data not shown). This result thus confirmed that the complex MGLP pattern described above resulted from variable combinations of acylation of mainly two oligosaccharide backbones, MGP 19,12 and MGP 20,12 , and, to a much lesser extent, MGP 20,11 and MGP 20,13 .…”
Section: Construction Of M Smegmatis and M Tuberculosis Glucosyltrasupporting
confidence: 81%
“…3B and 4B, the disruptions of Rv3032 and MSMEG2349 had significant impacts on the MGLP patterns of M. tuberculosis and M. smegmatis. H37Rv⌬Rv3032 accumulated polysaccharidic compounds with lower masses, consisting essentially of 17 Glc residues (MGP 17,9 , MGP 17,10 , MGP 17,11 ), with lesser quantities of MGP 16,10 , MGP 18,10 , MGP 18,11 , MGP 18,12 , and MGP 19,12 . More glucosylated forms of MGLP could not be detected in this strain.…”
Section: Construction Of M Smegmatis and M Tuberculosis Glucosyltramentioning
confidence: 99%
See 2 more Smart Citations
“…This organism, which also synthesizes an MGLP similar to that of mycobacteria, is phylogenetically related to these organisms [40]. Other species of Nocardia have been examined where this glycolipid has not been found [39].…”
Section: Mycobacteriummentioning
confidence: 99%